Efficacy and safety of perioperative analgesia in PENG block for children undergoing hip surgery with developmental dysplasia: study protocol for a randomized, double-blinded, non-inferiority trial - Mingzhe Xu; Yi He; Zhi Li; Bin Du (Trials)
Abstract Background Surgical intervention is critical in the treatment of hip developmental dysplasia in children. Perioperative analgesia, usually based on high opioid dosages, is frequently used in these patients. In some circumstances, regional anesthetic procedures such as caudal block and lumbar plexus block have also been used. Previous research has shown that pericapsular nerve group (PENG) block provides excellent anesthetic efficacy during open hip surgery in adults. PENG block is thought to provide a similar analgesia effect comparable to caudal block. Methods This study is a single-center, prospective, randomized, double-blinded, non-inferiority experiment that enrolled children aged 6 months to 7 years who were scheduled for developmental dysplasia hip surgery. Following general anesthesia and regional blocks (0.25% ropivacaine at a dose of 2.5 mg·kg−1 with epinephrine at a concentration of 1:200,000), 48 individuals will be randomly assigned to either the PENG or caudal groups. The primary outcome measure is the highest FLACC (face, legs, activity, crying, consolability) score achieved within 24 h of surgery. Secondary outcomes include intraoperative opioid consumption, analgesic dosage within 24 h of surgery, time to start rescue analgesia, number of PCA pump activations, time to remove SLIPA (streamlined liner of the pharynx airway), duration of regional block procedures, incidence of adverse events, plasma ropivacaine concentrations, and hospital stays and costs. All data will be collected by blinded investigators. The trial’s final results will be published in a peer-reviewed scientific journal. Discussion We expect this trial to provide some evidences that PENG block is safe and effective for perioperative analgesia in pediatric patients undergoing open hip surgery. Trial registration Chinese Clinical Trial Registry ChiCTR2100053128. Registered on November 12, 2021.